2007
DOI: 10.1071/ch07282
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-Aryloxazolidines via 1,3-Dipolar Cycloaddition Reaction of a Non-Stabilized Azomethine Ylide with Aromatic Aldehydes

Abstract: The 1,3-dipolar cycloaddition reaction of a non-stabilized azomethine ylide 4a, formed in situ from N-(methoxymethyl)-N-(trimethylsilylmethyl)benzylamine 5 and a catalytic amount of trifluoroacetic acid, with aromatic aldehydes 3 gives rise to N-benzyl-5-aryloxazolidines 1. Under these conditions, 4-hydroxybenzaldehyde 3p undergoes two-fold addition of azomethine ylide 4a to afford bis adduct 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Additionally, for 4-hydroxybenzaldehyde (2t), the main product was the bis adduct 174, isolated in 53% yield (Figure 2). Recently, a thorough exploration of the reactions of reagent 178 with aromatic and heteroaromatic aldehydes 2 was reported [133]. Firstly, it was found that generating the ylide by trifluoroacetic acid catalysis [131] in CH 2 Cl 2 at 25˝C in the presence of benzaldehyde (2a) afforded a 95% yield of the oxazolidine cycloadduct 173a (Scheme 45) (Table 23, entry 1), a higher yield than that reported using LiF to generate the ylide from reagent 178 [129].…”
Section: Desilylation Of α-Substituted Methyl(trimethylsilylmethyl)ammentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, for 4-hydroxybenzaldehyde (2t), the main product was the bis adduct 174, isolated in 53% yield (Figure 2). Recently, a thorough exploration of the reactions of reagent 178 with aromatic and heteroaromatic aldehydes 2 was reported [133]. Firstly, it was found that generating the ylide by trifluoroacetic acid catalysis [131] in CH 2 Cl 2 at 25˝C in the presence of benzaldehyde (2a) afforded a 95% yield of the oxazolidine cycloadduct 173a (Scheme 45) (Table 23, entry 1), a higher yield than that reported using LiF to generate the ylide from reagent 178 [129].…”
Section: Desilylation Of α-Substituted Methyl(trimethylsilylmethyl)ammentioning
confidence: 99%
“…The cycloaddition of ylide 172, generated by trifluoroacetic acid catalyzed decomposition of silylamine reagent 178, to a range of heteroaromatic aldehydes 2 was also explored with the only limitation appearing to be electron-rich aromatic aldehydes (Table 24) [133]. 2-Furan-, 2-thiopheneand 3-pyridine carboxaldehydes (2u-w) all underwent efficient cycloaddition under these conditions (Entries 1-3).…”
Section: Scheme 45mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the reaction of aldehydes 1 with sarcosine and paraformaldehyde leads to N-methyl-oxazolidines 2, 6 whereas their reaction with N-(methoxymethyl)-N-[(trimethylsilyl)methyl]benzylamine in the presence of a catalytic amount of trifluoroacetic acid gives N-benzyloxazolidines 3. 7 The starting aldehydes 1 are also known to participate in the generation of azomethine ylides, forming a mixture of regioisomers 4 and 4′ (Scheme 1). 1a Scheme 1 Reactions of aromatic aldehydes with nonstabilized azomethine ylides However, to the best of our knowledge, no studies on the reactions of azomethine ylides with such central organic compounds as saturated aliphatic aldehydes have been undertaken.…”
mentioning
confidence: 99%
“…In this case, the benzoyl protection was removed simultaneously by demethylenation of oxazolidine 2e under the action of hydrazine hydrate (Scheme 2, Table 1). An alternative method for the generation of a nonstabilized azomethine ylide from N-(methoxymethyl)-N-(trimethylsilylmethyl)benzylamine in the presence of trifluoroacetic acid, 12 followed by hydrazinolysis of oxazolidine 2j allowed us to obtain N-benzyl derivative 1j isolated as the hydrochloride. Application of this reaction to thiophene-2-carbaldehyde led to a two-step synthesis of 2-(benzylamino)-1-(thien-2-yl)ethanol (1k) in 71% yield (Scheme 3).…”
mentioning
confidence: 99%